N6-Methyladenosine RNA Modification in the Tumor Immune Microenvironment: Novel Implications for Immunotherapy - Guo, Liting; Yang, Hui; Zhou, Chenfei; Shi, Yan; Huang, Lei; Zhang, Jun (Frontiers in Immunology, 2021)
N6-methyladenosine (m6A) methylation is one of the most common modifications of RNA in eukaryotic cells, and is mainly regulated by m6A methyltransferases (writers), m6A demethylases (erasers), and m6A binding proteins (readers). Recently, accumulating evidence has shown that m6A methylation plays crucial roles in the regulation of the tumor immune microenvironment, greatly impacting the initiation, progression, and metastasis processes of various cancers. In this review we first briefly summarizes the m6A-related concepts and detection methods, and then describes in detail the associations of m6A methylation modification with various tumor immune components especially immune cells (e.g., regulatory T cells, dendritic cells, macrophages, and myeloid-derived suppressor cells) in a variety of cancers. We discuss the relationship between m6A methylation and cancer occurrence and development with the involvement of tumor immunity highlighted, suggesting novel markers and potential targets for molecular pathological diagnosis and immunotherapy of various cancers.